A high-foaming low-density composite sealing strip material and preparation method thereof
By blending ethylene propylene ternary rubber with ethylene-vinyl acetate copolymer and adding modified composite filler, the mechanical properties, flame retardant properties and UV aging resistance of the seal strips are improved, and the problems of easy deformation and aging of existing seal strips are solved, extending service life and improving overall performance.
Patent Information
- Application Number
- CN202510046299.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-13
AI Technical Summary
Existing foamed seal strips are prone to deformation and aging during use, resulting in degradation of sealing performance and insufficient flame retardant performance, which limits its application.
Ethylene propylene ternary rubber is blended with ethylene-vinyl acetate copolymer, and modified composite fillers are added, including acid chloride flame retardant additives and modified ultraviolet absorbers. By adding the modified composite fillers, the mechanical properties, flame retardant properties and UV aging resistance of the material are improved.
It significantly improves the mechanical properties, flame retardant properties and UV aging resistance of the sealing strip, extends the service life, and improves the overall performance of the sealing strip.
Smart Images

Figure SMS_3 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sealing strips, and in particular relates to a high-foaming low-density composite sealing strip material and a preparation method thereof. Background Art
[0002] Foam sealing strips are widely used in the automotive, home furnishing and other industries, mainly for sealing, heat insulation, shock absorption, dustproof, waterproof and decoration. Existing foam sealing strips are mainly made of EPDM rubber vulcanization foaming, and a small part is made of thermoplastic polyolefin elastomer, polyvinyl chloride, etc. High foam (low density) EPDM rubber sealing strips have good sealing performance, small deformation after long-term use, good high and low temperature resistance and weather resistance, reliable performance, low density and light weight, and occupy an important share in the foam sealing strip market.
[0003] In the processing technology of rubber materials, in order to increase the strength and volume of products and reduce costs, fillers such as carbon black, white carbon black and calcium carbonate are generally added. For foaming materials, due to the countless tiny pores inside, the larger pore area in the matrix is easy to become a stress concentration point and damage when subjected to external force. Therefore, it is very necessary to reinforce the foamed EPDM rubber with fillers, and the fillers added during the foaming process will become nucleation points, thereby promoting heterogeneous nucleation and increasing the pore density. However, the dispersion of inorganic fillers in composite materials becomes the key to the performance of the material, because inorganic fillers are prone to agglomeration, resulting in pore collapse and the formation of local large pores, which has an adverse effect on the mechanical properties of the material. In addition, the existing sealing strips have a single function during production, and the sealing strips are prone to deformation and aging when exposed to light for a long time, resulting in the breakage of the material molecular chain and the destruction of the molecular structure, which seriously affects the sealing performance, shock absorption performance and service life of the sealing strips. In addition, the existing foaming sealing strips have the defect of poor flame retardancy, which limits the further application of foaming sealing strips. Summary of the invention
[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a high-foamed low-density composite sealing strip material and a preparation method thereof, by blending EPDM rubber and ethylene-vinyl acetate copolymer, and adding modified composite fillers to give the material excellent mechanical properties, flame retardant properties and UV aging resistance.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A high-foaming low-density composite sealing strip material, comprising the following components in parts by weight: 60-90 parts of EPDM rubber, 5-15 parts of ethylene-vinyl acetate copolymer, 10-15 parts of modified composite filler, 3-5 parts of zinc oxide, 1-3 parts of stearic acid, 7-12 parts of paraffin oil, 2-5 parts of calcium oxide, 1-3 parts of accelerator, 1-2 parts of sulfur, and 5-8 parts of foaming agent;
[0007] The modified composite filler is prepared by chlorinating the flame retardant additive and the modified ultraviolet absorber with oxalyl chloride, and then grafting with the aminated composite filler, wherein the aminated composite filler is prepared by aminated silicon dioxide and titanium dioxide with γ-aminopropyltriethoxysilane;
[0008] The flame retardant additive is prepared by grafting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, salicylaldehyde and pentaethylenehexamine as raw materials, and its structural formula is:
[0009] ;
[0010] The modified ultraviolet absorber is prepared by substitution reaction of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and phenylphosphonyl dichloride, and its structural formula is:
[0011] .
[0012] Preferably, the accelerator is one of accelerator M, accelerator DM, accelerator TMTD, accelerator D, accelerator DTDM, accelerator BZ, or a mixture of several thereof; the foaming agent is one of azodicarbonamide, 4,4'-oxybisbenzenesulfonylhydrazide, N,N'-dinitrosopentamethylenetetramine, or a mixture of several thereof.
[0013] Preferably, the method for preparing the modified composite filler comprises the following steps:
[0014] A. Take an ethanol solution and adjust the pH value to 2-3 with oxalic acid, then add γ-aminopropyltriethoxysilane and mix evenly, let it stand for hydrolysis for 0.5-1h to obtain a hydrolyzate, take the ethanol solution in a reactor, add silicon dioxide, titanium dioxide and the hydrolyzate, place it in a water bath at 55-70°C for 0.5-1h, and after the reaction is completed, filter, wash and dry to prepare an amino composite filler;
[0015] B. Ultrasonic dispersion of the amino composite filler in toluene, add a mixed solution of acyl chloride flame retardant additive, acyl chloride modified ultraviolet absorber and toluene in a nitrogen atmosphere, stir and mix evenly, then add triethylamine, place at 55-70°C to react for 20-24h, and after the reaction is completed, filter, wash and dry to prepare a modified composite filler.
[0016] Preferably, in step A, the mass ratio of γ-aminopropyltriethoxysilane, silicon dioxide and titanium dioxide is 1-2:10-15:5-10.
[0017] Preferably, in step B, the mass ratio of the amination composite filler, the acylation flame retardant additive and the acylation modified ultraviolet absorber is 2-5:0.5-1:0.5-1.
[0018] Preferably, the method for preparing the acyl chloride flame retardant additive in step B comprises the following steps:
[0019] (1) Put pentaethylenehexamine and salicylaldehyde in a reactor, add anhydrous ethanol solvent, heat to 105-120°C, stir and react for 3-5 hours, then add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, continue stirring and react for 4-6 hours, after the reaction is completed, remove the solvent by rotary evaporation, wash, filter and dry to prepare a flame retardant additive;
[0020] (2) Put the flame retardant additive in a reactor, add acetone solvent, add oxalyl chloride in an ice-water bath under nitrogen protection, add triethylamine in batches during the reaction, remove the hydrogen chloride produced by the reaction, and terminate the reaction after 6 to 8 hours. After filtering, rotary evaporation and drying, the acyl chloride flame retardant additive is prepared.
[0021] Preferably, in step (1), the molar ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, salicylaldehyde and pentaethylenehexamine is 8-8.5:8-8.5:1.
[0022] Preferably, the preparation method of the acyl chloride modified ultraviolet absorber in step B comprises the following steps:
[0023] a. Take 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and phenylphosphonyl dichloride in a reactor, add tetrahydrofuran solvent and triethylamine, place in an ice bath and stir to react for 7-9 hours. After the reaction is completed, wash, filter and dry to prepare a modified ultraviolet absorber;
[0024] b. Take the modified UV absorber into a reactor, add acetone solvent, add oxalyl chloride in an ice-water bath under nitrogen protection, react for 3 to 4 hours and add triethylamine in batches, remove excess oxalyl chloride and hydrogen chloride produced by the reaction, filter, rotary evaporate and dry to prepare the chlorinated modified UV absorber.
[0025] Preferably, in step a, the molar ratio of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole to phenylphosphonic dichloride is 2-2.5:1.
[0026] The method for preparing the high-foamed low-density composite sealing strip material as described above comprises the following steps:
[0027] S1, adding parts by weight of EPDM rubber, ethylene-vinyl acetate copolymer, modified composite filler, zinc oxide, stearic acid, paraffin oil and calcium oxide into an internal mixer and mixing for 10-15 minutes at a mixing temperature of 130-160° C. to obtain a masterbatch;
[0028] S2. After the rubber material is cooled, mix it on an open mixing mill, first thin it through 2 to 3 times, wrap it with a roller, add parts by weight of sulfur, accelerator and foaming agent after the rubber layer is smooth, make a triangle wrap and thin it through 3 to 5 times, mix it evenly, and vulcanize it at 160 to 230°C for 5 to 10 minutes to prepare a high-foamed low-density composite sealing strip material.
[0029] Beneficial effects of the present invention:
[0030] The present invention uses EPDM rubber as a base rubber material and adds ethylene-vinyl acetate copolymer for blending. Ethylene-vinyl acetate copolymer is a high-quality elastomer with low density and low cost. When the ethylene-vinyl acetate copolymer is added to the EPDM rubber for foaming, the two have good compatibility and can significantly reduce the density of the foamed product. Moreover, by adding the modified composite filler, the material is endowed with excellent mechanical properties, flame retardant properties and UV aging resistance.
[0031] The invention uses 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide as a phosphorus-containing component to react with pentaethylenehexamine with a high nitrogen content to prepare a flame retardant additive containing nitrogen and phosphorus elements, which gives the material good flame retardant properties. At the same time, the invention uses a hydroxyl group in a 2-(2,4-dihydroxyphenyl)-2H-benzotriazole structure and chlorine atoms at both ends of phenylphosphonyl dichloride to undergo a substitution reaction to prepare a modified ultraviolet absorber containing a benzotriazole group and phosphorus elements, which gives the material good ultraviolet aging resistance and flame retardant properties.
[0032] The invention causes a substitution reaction between hydroxyl groups in the structures of a flame retardant additive and a modified ultraviolet absorber and oxalyl chloride to prepare an acyl chloride flame retardant additive and an acyl chloride modified ultraviolet absorber. In addition, the invention uses a silanol group in a γ-aminopropyltriethoxysilane structure to undergo a condensation reaction with hydroxyl groups on the surfaces of silicon dioxide and titanium dioxide after hydrolysis to prepare an amination composite filler of amination silicon dioxide and amination titanium dioxide. Then, the chlorine atoms in the structures of the acyl chloride flame retardant additive and the acyl chloride modified ultraviolet absorber react with amino groups in the structure of the amination composite filler to prepare a modified composite filler. Thus, the flame retardant additive and the modified ultraviolet absorber are grafted on the surfaces of silicon dioxide and titanium dioxide through a firm chemical bond, which is beneficial to the dispersion of the composite filler, prevents the generation of agglomeration, enhances the compatibility of the composite filler with a rubber matrix, thereby improving the mechanical properties of the material, and avoids the agglomeration of titanium dioxide to increase its particle size and affect the ultraviolet shielding efficiency. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1 A method for preparing an acyl chloride flame retardant additive comprises the following steps:
[0035] (1) 4.6 g of pentaethylenehexamine and 19.5 g of salicylaldehyde were placed in a reactor, 200 mL of anhydrous ethanol solvent was added, the temperature was raised to 110° C., and the mixture was stirred for 4 h. Then 34.6 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added, and the mixture was stirred for 5 h. After the reaction was completed, the solvent was removed by rotary evaporation, and the mixture was washed, filtered, and dried to prepare a flame retardant additive.
[0036] (2) Take 27.9 g of flame retardant additive into a reactor, add 100 mL of acetone solvent, add 10.2 g of oxalyl chloride in an ice-water bath under nitrogen protection, add 6 mL of triethylamine in batches during the reaction, remove the hydrogen chloride produced by the reaction, and terminate the reaction after 8 h. After filtering, rotary evaporation and drying, the acyl chloride flame retardant additive is prepared.
[0037] Example 2 A method for preparing an acyl chloride modified ultraviolet absorber comprises the following steps:
[0038] a. Take 10g of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and 3.9g of phenylphosphonyl dichloride in a reactor, add 50mL of tetrahydrofuran solvent and 7mL of triethylamine, place in an ice bath and stir to react for 8h. After the reaction is completed, wash, filter and dry to prepare a modified ultraviolet absorber;
[0039] b. Take 5.8g of modified UV absorber in a reactor, add 50mL of acetone solvent, add 2.5g of oxalyl chloride under ice-water bath and nitrogen protection, react for 4h and add 6mL of triethylamine in batches, remove excess oxalyl chloride and hydrogen chloride produced by the reaction, filter, rotary evaporate and dry to prepare the chlorinated modified UV absorber.
[0040] Example 3 A method for preparing a modified composite filler comprises the following steps:
[0041] A. Take 10 mL of 50% ethanol solution, adjust the pH value to 2 with oxalic acid, then add 1.2 g of γ-aminopropyltriethoxysilane and mix evenly, let it stand for hydrolysis for 1 hour to obtain a hydrolyzate, take 150 mL of 50% ethanol solution in a reactor, add 12 g of silicon dioxide, 8 g of titanium dioxide and the hydrolyzate, place it in a water bath at 65°C for 1 hour, and after the reaction is completed, filter, wash and dry to prepare an amino composite filler;
[0042] B. Take 10g of the amino composite filler and ultrasonically disperse it in 200mL of toluene. Add a mixed solution of 2g of the acyl chloride flame retardant additive prepared in Example 1, 2g of the acyl chloride modified ultraviolet absorber prepared in Example 2 and 50mL of toluene in a nitrogen atmosphere, stir and mix evenly, then add 7mL of triethylamine, place at 70°C to react for 24h, and after the reaction is completed, filter, wash and dry to prepare a modified composite filler.
[0043] Example 4 A high-foamed, low-density composite sealing strip material comprises the following components in parts by weight:
[0044] 62 parts of EPDM rubber, 7 parts of ethylene-vinyl acetate copolymer, 10 parts of the modified composite filler prepared in Example 3, 3 parts of zinc oxide, 1.5 parts of stearic acid, 8 parts of paraffin oil, 2 parts of calcium oxide, 1 part of accelerator M, 1 part of sulfur, and 5 parts of azodicarbonamide, a foaming agent.
[0045] The preparation method of the above-mentioned high-foaming low-density composite sealing strip material comprises the following steps:
[0046] S1, adding parts by weight of EPDM rubber, ethylene-vinyl acetate copolymer, modified composite filler, zinc oxide, stearic acid, paraffin oil and calcium oxide into an internal mixer and mixing for 15 minutes at a mixing temperature of 145° C. to obtain a masterbatch;
[0047] S2. After the rubber material is cooled, it is mixed on an open mixing mill, thinned twice, rolled, and after the rubber layer is smooth, sulfur, accelerator and foaming agent are added by weight, and triangular rolls are rolled and thinned 5 times. After mixing evenly, it is vulcanized at 185°C for 10 minutes to prepare a high-foamed low-density composite sealing strip material.
[0048] Example 5 A high-foaming, low-density composite sealing strip material comprises the following components in parts by weight:
[0049] 77 parts of EPDM rubber, 12 parts of ethylene-vinyl acetate copolymer, 12 parts of the modified composite filler prepared in Example 3, 4 parts of zinc oxide, 2 parts of stearic acid, 10 parts of paraffin oil, 3 parts of calcium oxide, 2 parts of accelerator M, 1.5 parts of sulfur, and 7 parts of azodicarbonamide, a foaming agent.
[0050] The preparation method of the above-mentioned high-foamed low-density composite sealing strip material is the same as that of Example 4.
[0051] Example 6 A high-foaming, low-density composite sealing strip material comprises the following components in parts by weight:
[0052] 87 parts of EPDM rubber, 14 parts of ethylene-vinyl acetate copolymer, 15 parts of the modified composite filler prepared in Example 3, 5 parts of zinc oxide, 3 parts of stearic acid, 12 parts of paraffin oil, 4 parts of calcium oxide, 2.5 parts of accelerator M, 2 parts of sulfur, and 8 parts of azodicarbonamide, a foaming agent.
[0053] The preparation method of the above-mentioned high-foamed low-density composite sealing strip material is the same as that of Example 4.
[0054] Comparative Example 1 A method for preparing a modified composite filler comprises the following steps:
[0055] A. Take 10 mL of 50% ethanol solution, adjust the pH value to 2 with oxalic acid, then add 1.2 g of γ-aminopropyltriethoxysilane and mix evenly, let it stand for hydrolysis for 1 hour to obtain a hydrolyzate, take 150 mL of 50% ethanol solution in a reactor, add 12 g of silicon dioxide, 8 g of titanium dioxide and the hydrolyzate, place it in a water bath at 65°C for 1 hour, and after the reaction is completed, filter, wash and dry to prepare an amino composite filler;
[0056] B. Take 10g of the amino composite filler and ultrasonically disperse it in 200mL of toluene. Add a mixed solution of 2g of the acyl chloride modified ultraviolet absorber prepared in Example 2 and 50mL of toluene in a nitrogen atmosphere, stir and mix evenly, then add 3mL of triethylamine, place it at 70°C to react for 24h, and after the reaction is completed, filter, wash and dry to prepare a modified composite filler.
[0057] Comparative Example 2 A method for preparing a modified composite filler comprises the following steps:
[0058] A. Take 10 mL of 50% ethanol solution, adjust the pH value to 2 with oxalic acid, then add 1.2 g of γ-aminopropyltriethoxysilane and mix evenly, let it stand for hydrolysis for 1 hour to obtain a hydrolyzate, take 150 mL of 50% ethanol solution in a reactor, add 12 g of silicon dioxide, 8 g of titanium dioxide and the hydrolyzate, place it in a water bath at 65°C for 1 hour, and after the reaction is completed, filter, wash and dry to prepare an amino composite filler;
[0059] B. Take 10g of the amino composite filler and ultrasonically disperse it in 200mL of toluene. Add a mixed solution of 2g of the acyl chloride flame retardant additive prepared in Example 1 and 50mL of toluene in a nitrogen atmosphere, stir and mix evenly, then add 5mL of triethylamine, place it at 70°C to react for 24h, and after the reaction is completed, filter, wash and dry to prepare a modified composite filler.
[0060] Comparative Example 3 A high-foamed low-density composite sealing strip material comprises the following components in parts by weight:
[0061] 87 parts of EPDM rubber, 14 parts of ethylene-vinyl acetate copolymer, 15 parts of the modified composite filler prepared in Comparative Example 1, 5 parts of zinc oxide, 3 parts of stearic acid, 12 parts of paraffin oil, 4 parts of calcium oxide, 2.5 parts of accelerator M, 2 parts of sulfur, and 8 parts of azodicarbonamide, a foaming agent.
[0062] The preparation method of the above-mentioned high-foamed low-density composite sealing strip material is the same as that of Example 4.
[0063] Comparative Example 4 A high-foamed low-density composite sealing strip material comprises the following components in parts by weight:
[0064] 87 parts of EPDM rubber, 14 parts of ethylene-vinyl acetate copolymer, 15 parts of the modified composite filler prepared in Comparative Example 2, 5 parts of zinc oxide, 3 parts of stearic acid, 12 parts of paraffin oil, 4 parts of calcium oxide, 2.5 parts of accelerator M, 2 parts of sulfur, and 8 parts of azodicarbonamide, a foaming agent.
[0065] The preparation method of the above-mentioned high-foamed low-density composite sealing strip material is the same as that of Example 4.
[0066] Comparative Example 5 A high-foamed low-density composite sealing strip material comprises the following components in parts by weight:
[0067] 87 parts of EPDM rubber, 14 parts of ethylene-vinyl acetate copolymer, 9 parts of silicon dioxide, 6 parts of titanium dioxide, 5 parts of zinc oxide, 3 parts of stearic acid, 12 parts of paraffin oil, 4 parts of calcium oxide, 2.5 parts of accelerator M, 2 parts of sulfur, and 8 parts of azodicarbonamide, a foaming agent.
[0068] The preparation method of the above-mentioned high-foamed low-density composite sealing strip material is the same as that of Example 4.
[0069] Performance Testing
[0070] The sealing strip materials prepared in Examples 4-6 and Comparative Examples 3-5 were subjected to performance testing:
[0071] (1) Tensile and flame retardant properties testing: The tensile properties were tested using an electronic tensile testing machine in accordance with GB / T 528-2009, using dumbbell-shaped tensile specimens at a tensile rate of 500 mm / min. The flame retardant properties were tested using the limiting oxygen index test, and the data results are shown in Table 1.
[0072] (2) UV aging resistance and foaming performance test: The light source is a 20W UV lamp, emitting short-wave UV light with a characteristic wavelength of 253.7nm. The UV irradiation intensity at 20cm from the vertical center of the lamp tube is 1400μw / cm 2The sample was placed in a fixed position parallel to the light source and UV aged for 200h, 400h and 800h, and the change rate of tensile strength and elongation at break were tested; the apparent density of the material was tested according to ASTM D 792, and the data results are shown in Table 1.
[0073] Table 1 Test results of sample performance
[0074]
[0075] It can be seen from the data in Table 1 that the sealing strip materials prepared in Examples 4-6 of the present invention have low apparent density and high pore volume fraction, and all have the characteristics of high tensile strength and not easy to break. After aging for 200h, 400h and 800h, they still have high tensile strength and elongation at break, indicating that the sealing strip material has excellent resistance to ultraviolet aging, and has a high limiting oxygen index and excellent flame retardant properties. Among them, the modified composite filler added in Comparative Example 3 does not contain flame retardant additive components, and its measured limiting oxygen index is significantly lower than that of Examples 4-6, indicating that the addition of flame retardant additives can improve the flame retardant properties of the material. The modified composite filler added in Comparative Example 4 does not contain modified UV absorber components, and its measured tensile strength change rate, elongation at break change rate and limiting oxygen index are lower than those of Examples 4-6, indicating that the addition of modified UV absorbers can improve the material's UV aging resistance and flame retardant properties to a certain extent. In Comparative Example 5, silica and titanium dioxide are simply mixed, and its measured UV aging resistance and flame retardant properties are most significantly lower than those of Examples 4-6, and due to the agglomeration phenomenon of silica and titanium dioxide, its tensile strength and elongation at break are lower than those of Examples 4-6.
[0076] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0077] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A high-foamed low-density composite sealing strip material, characterized in that: The invention comprises the following components in parts by weight: 60-90 parts of EPDM rubber, 5-15 parts of ethylene-vinyl acetate copolymer, 10-15 parts of modified composite filler, 3-5 parts of zinc oxide, 1-3 parts of stearic acid, 7-12 parts of paraffin oil, 2-5 parts of calcium oxide, 1-3 parts of accelerator, 1-2 parts of sulfur and 5-8 parts of foaming agent; The modified composite filler is prepared by chlorinating the flame retardant additive and the modified ultraviolet absorber with oxalyl chloride, and then grafting with the aminated composite filler, wherein the aminated composite filler is prepared by simultaneously aminated silicon dioxide and titanium dioxide with γ-aminopropyltriethoxysilane; The flame retardant additive is prepared by grafting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, salicylaldehyde and pentaethylenehexamine as raw materials, and its structural formula is: ; The modified ultraviolet absorber is prepared by substitution reaction of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and phenylphosphonyl dichloride, and its structural formula is: 。 2. The high-foamed low-density composite sealing strip material according to claim 1, characterized in that: The accelerator is one of accelerator M, accelerator DM, accelerator TMTD, accelerator D, accelerator DTDM, and accelerator BZ, or a mixture of several of them; the foaming agent is one of azodicarbonamide, 4,4'-oxybisbenzenesulfonylhydrazide, and N,N'-dinitrosopentamethylenetetramine, or a mixture of several of them.
3. The high-foamed low-density composite sealing strip material according to claim 1, characterized in that: The preparation method of the modified composite filler comprises the following steps: A. Take an ethanol solution and adjust the pH value to 2-3 with oxalic acid, then add γ-aminopropyltriethoxysilane and mix evenly, let it stand for hydrolysis for 0.5-1h to obtain a hydrolyzate, take the ethanol solution in a reactor, add silicon dioxide, titanium dioxide and the hydrolyzate, place it in a water bath at 55-70°C for 0.5-1h, and after the reaction is completed, filter, wash and dry to prepare an amino composite filler; B. Ultrasonic dispersion of the amino composite filler in toluene, add a mixed solution of acyl chloride flame retardant additive, acyl chloride modified ultraviolet absorber and toluene in a nitrogen atmosphere, stir and mix evenly, then add triethylamine, place at 55-70°C to react for 20-24h, and after the reaction is completed, filter, wash and dry to prepare a modified composite filler.
4. The high-foamed low-density composite sealing strip material according to claim 3, characterized in that: In the step A, the mass ratio of γ-aminopropyltriethoxysilane, silicon dioxide and titanium dioxide is 1-2:10-15:5-10.
5. The high-foamed low-density composite sealing strip material according to claim 3, characterized in that: In the step B, the mass ratio of the amination composite filler, the acyl chloride flame retardant additive and the acyl chloride modified ultraviolet absorber is 2-5:0.5-1:0.5-1.
6. The high-foamed low-density composite sealing strip material according to claim 3, characterized in that: The preparation method of the acyl chloride flame retardant additive in step B comprises the following steps: (1) Put pentaethylenehexamine and salicylaldehyde in a reactor, add anhydrous ethanol solvent, heat to 105-120°C, stir and react for 3-5 hours, then add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, continue stirring and react for 4-6 hours, after the reaction is completed, remove the solvent by rotary evaporation, wash, filter and dry to prepare a flame retardant additive; (2) Put the flame retardant additive in a reactor, add acetone solvent, add oxalyl chloride in an ice-water bath under nitrogen protection, add triethylamine in batches during the reaction, remove the hydrogen chloride produced by the reaction, and terminate the reaction after 6 to 8 hours. After filtering, rotary evaporation and drying, the acyl chloride flame retardant additive is prepared.
7. The high-foamed low-density composite sealing strip material according to claim 6, characterized in that: In the step (1), the molar ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, salicylaldehyde and pentaethylenehexamine is 8-8.5:8-8.5:
1.
8. The high-foamed low-density composite sealing strip material according to claim 3, characterized in that: The preparation method of the acyl chloride modified ultraviolet absorber in step B comprises the following steps: a. Take 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and phenylphosphonyl dichloride in a reactor, add tetrahydrofuran solvent and triethylamine, place in an ice bath and stir to react for 7-9 hours. After the reaction is completed, wash, filter and dry to prepare a modified ultraviolet absorber; b. Take the modified UV absorber into a reactor, add acetone solvent, add oxalyl chloride in an ice-water bath under nitrogen protection, react for 3 to 4 hours and add triethylamine in batches, remove excess oxalyl chloride and hydrogen chloride produced by the reaction, filter, rotary evaporate and dry to prepare the chlorinated modified UV absorber.
9. The high-foamed low-density composite sealing strip material according to claim 8, characterized in that: In the step a, the molar ratio of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole to phenylphosphonic acid dichloride is 2-2.5:
1.
10. A method for preparing a high-foamed low-density composite sealing strip material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, adding parts by weight of EPDM rubber, ethylene-vinyl acetate copolymer, modified composite filler, zinc oxide, stearic acid, paraffin oil and calcium oxide into an internal mixer and mixing for 10-15 minutes at a mixing temperature of 130-160° C. to obtain a masterbatch; S2. After the rubber material is cooled, mix it on an open mixing mill, first thin it through 2 to 3 times, wrap it with a roller, add parts by weight of sulfur, accelerator and foaming agent after the rubber layer is smooth, make a triangle wrap and thin it through 3 to 5 times, mix it evenly, and vulcanize it at 160 to 230°C for 5 to 10 minutes to prepare a high-foamed low-density composite sealing strip material.
Citation Information
Patent Citations
Graphene-modified high-molecular soft anti-deformation composite foaming material and preparation method thereof
CN107254096A
Flame retardant composite cable
CN108690279A